Acousto-optic modulators for a controlled frequency shift of light beams in optical and microwave cold-atom frequency standards. (September 2019) - Epikhin, V.M.; Baryshev, V.N.; Slyusarev, S.N.; Aprelev, A.V.; Blinov, I.Yu.
Abstract: A series of specialised acousto-optic modulators/frequency shifters based on paratellurite (TeO2 ) single crystals is developed for systems of laser cooling and frequency stabilisation of laser sources in optical and microwave frequency standards based on cold strontium, rubidium and caesium atoms. The methods of calculation and optimisation of the main parameters of acousto-optic modulators are considered; their basic technical characteristics are experimentally investigated in the spectral range of optical radiation 460 – 900 nm and in the frequency shift range of 5 – 400 MHz. The modulators have a high diffraction efficiency, low power consumption and the ability to work with linearly and randomly polarised optical radiation.